1989
DOI: 10.1093/carcin/10.5.813
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate dehydrogenase deficiency and cancer in a Sardinian male population: a case-control study

Abstract: A case-control study was conducted to test the hypothesis whether the genetic condition of glucose-6-phosphate dehydrogenase (G6PD) deficiency is associated with a reduced risk of cancer. One hundred and eighty seven male cancer patients admitted to hospitals in Cagliari (Sardinia, Italy), between November 1984 and March 1986, were compared with 186 male patients with other diseases, except hemolytic anemia, admitted to the same hospitals in the same period. In contrast to previous reports, our study found no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…First, several studies have shown that G6PD deficiency, an X-linked condition affecting hundreds of millions of men, does not reduce cancer risk despite a 90% reduction of enzyme activity in many individuals [21,22]. Second, transketolase activity is highly correlated with the rate of tumor growth, and expression of the transketolase isoform TKTL1 in colon, urothelial and ovarian cancers correlates with invasiveness and poor patient outcome [23,24••,25••].…”
Section: How Do Tumor Cells Divert Glycolytic Carbon Towards Ribose-5mentioning
confidence: 99%
“…First, several studies have shown that G6PD deficiency, an X-linked condition affecting hundreds of millions of men, does not reduce cancer risk despite a 90% reduction of enzyme activity in many individuals [21,22]. Second, transketolase activity is highly correlated with the rate of tumor growth, and expression of the transketolase isoform TKTL1 in colon, urothelial and ovarian cancers correlates with invasiveness and poor patient outcome [23,24••,25••].…”
Section: How Do Tumor Cells Divert Glycolytic Carbon Towards Ribose-5mentioning
confidence: 99%
“…Data regarding association of G6PDH deficiency with cancer are controversial, because some studies demonstrated that G6PDH-deficient patients may additionally suffer from cancer (Pavel et al, 2003), while others state opposite (Cocco et al, 1989(Cocco et al, , 2007. Nevertheless, both situations are possible.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…[ 19 ] Further, large epidemiological studies conducted in Sardinia between 1980s and 1990s supported an inverse relationship between G6PD deficiency and lower cancer mortality in men. [ 20 , 21 ] However, additional investigations yielded inconclusive results. [ 22 – 24 ] After more than half a century of research, the hypothesis of a negative correlation between G6PD deficiency and cancer susceptibility is still insufficiently supported by empirical evidence.…”
Section: Introductionmentioning
confidence: 99%